Autosomal dominant tubulointerstitial kidney disease: A review - Živná, Martina; Kidd, Kendrah O; Barešová, Veronika; Hůlková, Helena; Kmoch, Stanislav; Bleyer, Anthony J (American journal of medical genetics. Part C, Seminars in medical genetics, 2022)
The clinical characteristics of autosomal dominant tubulointerstitial kidney disease (ADTKD) include bland urinary sediment, slowly progressive chronic kidney disease (CKD) with many patients reaching end stage renal disease (ESRD) between age 20 and 70 years, and autosomal dominant inheritance. Due to advances in genetic diagnosis, ADTKD is becoming increasingly recognized as a cause of CKD. Pathogenic variants in UMOD, MUC1, and REN are the most common causes of ADTKD. ADTKD-UMOD is also associated with hyperuricemia and gout. ADTKD-REN often presents in childhood with mild hypotension, CKD, hyperkalemia, acidosis, and anemia. ADTKD-MUC1 patients present only with CKD. This review describes the pathophysiology, genetics, clinical manifestation, and diagnosis for ADTKD, with an emphasis on genetic testing and genetic counseling suggestions for patients.
Keywords: MUC1; Humans; lidé středního věku; mutace; mladý dospělý; dospělí; Aged; Uromodulin; senioři; lidé; chronická renální insuficience; Adult; Middle Aged; Autosomal Dominant Tubulointerstitial Kidney Disease; uromodulin; Young Adult; UMOD; genetické testování; Genetic Testing; Mutation; Renal Insufficiency, Chronic; REN